Preoperative T1 Slope More Than 40° as a Risk Factor of Correction Loss in Patients With Adult Spinal Deformity. Issue 19 (1st October 2016) - Oe, Shin; Yamato, Yu; Togawa, Daisuke; Kurosu, Kenta; Mihara, Yuki; Banno, Tomohiro; Yasuda, Tatsuya; Kobayashi, Sho; Hasegawa, Tomohiko; Matsuyama, Yukihiro
Abstract : Study Design: A retrospective study of surgical outcomes of adult spinal deformity (ASD) cases. Objective: The aim of the study was to investigate the effects of high T1 slope (T1S) on surgical outcomes in patients with ASD. Summary of Background Data: Few studies have evaluated the surgical outcomes of patients with ASD with cervical deformities. Methods: Eighty-eight patients with ASD who underwent posterior spinal corrective fusion were assigned to either group A (T1S <40°) or group B (T1S ≥40°). Whole-spine standing radiographs of both groups were preoperatively assessed: at first standing after the surgery and at 1 and 2 years postoperatively. Results: There were 56 patients in group A and 32 in group B. The preoperative C7 sagittal vertical axis (SVA) improved from 61 to 41 mm in group A and from 161 to 64 mm in group B at first standing after the surgery. C7 SVA at 2 years after the surgery was, however, 57 mm in group A and 98 mm in group B because of correction loss ( P  = 0.003). T1S measurements before and immediately after the surgery and 2 years after the surgery were, however, 25°, 23°, and 27° in group A and 53°, 36°, and 41° in group B, respectively. There were no significant differences among measurements in group A. Those in group B were, however, significantly improved in the first standing, but T1S of 40° or higher deteriorated toward 2 years after the surgery. Conclusion: Among patients with T1S of 40° or higher, C7 SVA improved immediately after the surgery but worsened at 2 years after the surgery. These results suggested that cervicothoracic parameters were important predictors of correction loss. Level of Evidence: 4